Statins act as transient type I interferon inhibitors to enable the antitumor activity of modified vaccinia Ankara viral vectors. Issue 7 (28th July 2021) - Tenesaca, Shirley; Vasquez, Marcos; Alvarez, Maite; Otano, Itziar; Fernandez-Sendin, Myriam; Di Trani, Claudia Augusta; Ardaiz, Nuria; Gomar, Celia; Bella, Angela; Aranda, Fernando; Medina-Echeverz, José; Melero, Ignacio; et al.
Abstract : Background: Modified vaccinia virus Ankara (MVA) are genetically engineered non-replicating viral vectors. Intratumoral administration of MVA induces a cyclic GMP-AMP synthase-mediated type I interferon (IFN) response and the production of high levels of the transgenes engineered into the viral genome such as tumor antigens to construct cancer vaccines. Although type I IFNs are essential for establishing CD8-mediated antitumor responses, this cytokine family may also give rise to immunosuppressive mechanisms. Methods: In vitro assays were performed to evaluate the activity of simvastatin and atorvastatin on type I IFN signaling and on antigen presentation. Surface levels of IFN α/β receptor 1, endocytosis of bovine serum albumin-fluorescein 5 (6)-isothiocyanate, signal transducer and activator of transcription (STAT) phosphorylation, and real-time PCR of IFN-stimulated genes were assessed in the murine fibroblast cell line L929. In vivo experiments were performed to characterize the effect of simvastatin on the MVA-induced innate immune response and on the antitumor effect of MVA-based antitumor vaccines in B16 melanoma expressing ovalbumin (OVA) and Lewis lung carcinoma (LLC)-OVA tumor models. RNAseq analysis, depleting monoclonal antibodies, and flow cytometry were used to evaluate the MVA-mediated immune response. Results: In this work, we identified commonly prescribed statins as potent IFNα pharmacological inhibitors due to their ability to reduce surface expression levels of IFN-α/β receptor 1 and to reduce clathrin-mediated endocytosis. Simvastatin and atorvastatin efficiently abrogated for 8 hours the transcriptomic response to IFNα and enhanced the number of dendritic cells presenting an OVA-derived peptide bound to major histocompatibility complex (MHC) class I. In vivo, intraperitoneal or intramuscular administration of simvastatin reduced the inflammatory response mediated by peritumoral administration of MVA and enhanced the antitumor activity of MVA encoding tumor-associated antigens. The synergistic antitumor effects critically depend on CD8 + cells, whereas they were markedly improved by depletion of CD4 + lymphocytes, T regulatory cells, or NK cells. Either MVA-OVA alone or combined with simvastatin augmented B cells, CD4 + lymphocytes, CD8 + lymphocytes, and tumor-specific CD8 + in the tumor-draining lymph nodes. However, only the treatment combination increased the numbers of these lymphocyte populations in the tumor microenvironment and in the spleen. Conclusion: In conclusion, blockade of IFNα functions by simvastatin markedly enhances lymphocyte infiltration and the antitumor activity of MVA, prompting a feasible drug repurposing.